THE EFFECT OF SOCIAL MEDIA ON INCREASING PRODUCT SALES: A CASE STUDY OF MSMES IN INDONESIA - Silvia Ekasari; Susilo Utomo; Rina Apriliani (INTERNATIONAL JOURNAL OF FINANCIAL ECONOMICS, 2025)
The influence of social media on increasing sales of MSME products in Indonesia is seen in the ability of platforms such as Instagram, Facebook, and WhatsApp to expand market reach, increase product visibility, and build closer relationships with customers. Through interactive content, paid advertising, and collaboration with influencers, MSMEs can significantly increase sales and customer loyalty. Proper and consistent use of social media has proven to be an effective marketing strategy for the success of MSMEs in the digital era. The study in this research uses the literature method. The results show that effective use of social media can increase the visibility and market reach of MSMEs. Platforms such as Instagram, Facebook, and WhatsApp allow MSMEs to promote products more widely with interesting and interactive content. In addition, social media also allows MSMEs to build closer relationships with customers through direct interaction, get feedback, and increase customer loyalty. The study also identified that the use of paid advertising and collaboration with local influencers has a positive impact on sales. In conclusion, social media has a significant role in supporting the growth and success of MSMEs in Indonesia, depending on effective and consistent strategies.